2012
DOI: 10.5792/ksrr.2012.24.4.187
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Treatment for Osteoarthritic Knee

Abstract: Arthroscopic treatment for osteoarthritis of the knee has been widely performed as one of the surgical options, in spite of persisting concerns regarding its efficacy. Arthroscopic debridement is a general term that is used to cover many procedures, including lavage, partial meniscectomy, removal of loose body, synovectomy, chondroplasty, removal of offending osteophytes, and/or microfracture. Recently, the role of arthroscopy in managing the osteoarthritic knee has been challenged by elusive consensus on its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 36 publications
(37 reference statements)
0
13
0
1
Order By: Relevance
“…However, the surgeon may consider arthroscopy in these patients under certain circumstances. Consistent symptomatology secondary to a specific mechanism or movement with or without mechanical symptoms that localises well to the joint line makes meniscal pathology more likely 61. Loose bodies can also be removed with arthroscopy to prevent mechanical symptoms or loss of joint motion.…”
Section: Patient Selectionmentioning
confidence: 99%
“…However, the surgeon may consider arthroscopy in these patients under certain circumstances. Consistent symptomatology secondary to a specific mechanism or movement with or without mechanical symptoms that localises well to the joint line makes meniscal pathology more likely 61. Loose bodies can also be removed with arthroscopy to prevent mechanical symptoms or loss of joint motion.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Most orthopedic surgeons include arthroscopic surgery as a treatment modality for patients with mild or moderate knee OA. Arthroscopic surgery for knee OA may delay joint degeneration to maintain moderate activity and allow for future reconstruction, particularly for patients with mild to moderate OA ( 21 , 22 ). However, the treatment cannot reverse or stop the pathological process of OA or prevent its continuous development.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that radiofrequency-based therapies prevent damage to the cartilage and provide a smoothing effect without further fibrillation. Traditionally, surgeons have avoided radio-frequency based therapies because of fears of chondrocyte death from high temperature [11,12,[16][17][18][19][20].…”
Section: Open Accessmentioning
confidence: 99%